2019
DOI: 10.18203/2319-2003.ijbcp20190091
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices towards pharmacovigilance among health care professionals in a teaching and general hospital of South India

Abstract: Background: Pharmacovigilance is the science and activities relating to detection, monitoring, assessment, understanding and prevention of adverse effects or any other drug related problem from any pharmaceutical products. The core purpose of pharmacovigilance is to enhance patient care and generate the evidence based information on safety of medicines. The objective of present study was to evaluate the knowledge, attitude and practices of the healthcare professionals about pharmacovigilance and to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…11,27 Several studies measuring physicians' attitude regarding ADR reporting concluded that 80-95% of the agreement was seen among physicians that ADR reporting contributed toward patient safety, and the benefit was passed on to the patients. 28 Our study also found that 97.8% of physicians agreed that ADR reporting contributes to patient safety.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…11,27 Several studies measuring physicians' attitude regarding ADR reporting concluded that 80-95% of the agreement was seen among physicians that ADR reporting contributed toward patient safety, and the benefit was passed on to the patients. 28 Our study also found that 97.8% of physicians agreed that ADR reporting contributes to patient safety.…”
Section: Discussionsupporting
confidence: 65%
“…There is another study in India with similar results. 28 This suggests the possibility of the growing acceptance of physicians toward the role of other healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation